Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1177/1529100619888860
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Assessments in Legal Contexts: Are Courts Keeping “Junk Science” Out of the Courtroom?

Abstract: In this article, we report the results of a two-part investigation of psychological assessments by psychologists in legal contexts. The first part involves a systematic review of the 364 psychological assessment tools psychologists report having used in legal cases across 22 surveys of experienced forensic mental health practitioners, focusing on legal standards and scientific and psychometric theory. The second part is a legal analysis of admissibility challenges with regard to psychological assessments. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 93 publications
0
49
0
9
Order By: Relevance
“…This is all the more worrisome considering that, even if they are mentioned in written judgments, the assessment of witness credibility is rarely reviewed by appellate courts because, amongst other thing, they cannot "see and hear" the witnesses as judges previously did (Timony, 2000;Denault, 2015). Therefore, judges receive very little feedback and, as a consequence, could read manuals, and attend seminars promoting unfounded, discredited and pseudoscientific claims, all in good faith, throughout their career, without ever being told that, in fact, what they learned is unproven and amounts to nothing more than "junk science" (DeMatteo et al, 2019;Neal et al, 2019).…”
Section: The Detrimental Effects Of Misconceptions About Nonverbal Cumentioning
confidence: 99%
“…This is all the more worrisome considering that, even if they are mentioned in written judgments, the assessment of witness credibility is rarely reviewed by appellate courts because, amongst other thing, they cannot "see and hear" the witnesses as judges previously did (Timony, 2000;Denault, 2015). Therefore, judges receive very little feedback and, as a consequence, could read manuals, and attend seminars promoting unfounded, discredited and pseudoscientific claims, all in good faith, throughout their career, without ever being told that, in fact, what they learned is unproven and amounts to nothing more than "junk science" (DeMatteo et al, 2019;Neal et al, 2019).…”
Section: The Detrimental Effects Of Misconceptions About Nonverbal Cumentioning
confidence: 99%
“…Given the rate at which expert testimony is being offered by psychologists (see Melton et al, 2018), examining whether the assessment methods used by psychologists satisfy the Daubert criteria has clear importance. Neal, Slobogin, Saks, Faigman, and Geisinger (2019) answered the call in their ambitious, rigorous, and timely study of the admissibility of psychological assessment tools. In their article, Neal et al (2019) report on the results of their two-part investigation of psychological assessment tools in legal contexts.…”
Section: Psychological Sciencementioning
confidence: 99%
“…Neal, Slobogin, Saks, Faigman, and Geisinger (2019) answered the call in their ambitious, rigorous, and timely study of the admissibility of psychological assessment tools. In their article, Neal et al (2019) report on the results of their two-part investigation of psychological assessment tools in legal contexts. Using the results from 23 previous surveys of forensic mental health professionals, they first conducted a systematic review of the 364 psychological assessment tools that psychologists have reported using in legal contexts.…”
Section: Psychological Sciencementioning
confidence: 99%
See 2 more Smart Citations